(untitled) (ModaPalavra e-periódico, 2014)
With this text we intend to discuss about design, if there are assumptions to create and if the rapprochement between fashion designer and creators of other arts is legitimate. For this, we have specifically alluded to the clothe object, especially for its emblematic character within the fashion system. We brought to this debate critical thinkers and contemporary classics. Beyond the discussion of the art and technique boundaries, we assume that if the world change by man, the same man is a creator, and if he does, it is because he brings impulse and capacity for such. So our interest are less quantify and qualify such creations and more reflect on the creative act itself.